2019
DOI: 10.1016/j.jenvman.2019.109534
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and community fisheries in the arctic: A case study from Pangnirtung, Canada

Abstract: Coastal fishery systems in the Arctic are undergoing rapid change. This paper examines the ways in which Inuit fishers experience and respond to such change, using a case study from Pangnirtung, Canada. The work is based on over two years of fieldwork, during which semistructured interviews (n=62), focus group discussions (n=6, 31 participants) and key informant interviews (n=25) were conducted. The changes that most Inuit fishers experience are: changes in sea-ice conditions, Inuit people themselves, the land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 76 publications
2
52
0
Order By: Relevance
“…Coping strategies are typically linked to more moderate changes and increasing variability, 35 which in the case of shifting stocks could include declines in species abundance and new species occurrences. Coping strategies are often reactive or ex post facto as opposed to anticipatory, 38 and they keep the SES functioning in the original state by resisting the impacts of climate change.…”
Section: Ses Changesmentioning
confidence: 99%
See 4 more Smart Citations
“…Coping strategies are typically linked to more moderate changes and increasing variability, 35 which in the case of shifting stocks could include declines in species abundance and new species occurrences. Coping strategies are often reactive or ex post facto as opposed to anticipatory, 38 and they keep the SES functioning in the original state by resisting the impacts of climate change.…”
Section: Ses Changesmentioning
confidence: 99%
“…30 These strategies tend to be more anticipatory, but they can also be reactive. 35 At the individual level, an adapting strategy will involve systemic change (e.g., changing gear and/ or targeting a new species). 24 At the collective level, recent research has found that the configuration of social interactions plays a crucial role in the adaptation process, where adapting (and transforming) actions involve reorganization of social networks.…”
Section: Ses Changesmentioning
confidence: 99%
See 3 more Smart Citations